A systematic review of geographic differences in knee phenotypes based on the coronal plane alignment of the knee (CPAK) classification - Guanghui Zhao; Chengyuan Ma; Zifan Luo; Jianbing Ma; Jianpeng Wang (Arthroplasty)
Abstract Background The extent of geographic variation in knee phenotypes remains insufficiently documented. This systematic review intends to elucidate the regional disparities in the distribution of Coronal Plane Alignment of the Knee (CPAK) types across different geographic areas. Methods A systematic review of the literature was conducted in adherence to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Studies reporting the distribution of knee phenotypes, as classified by the CPAK system, in both healthy and arthritic populations, were included in the analysis. Based on the methods in the literature, the Hoy Risk of Bias Tool was used to assess the methodological quality of the included studies. To compare geographical differences in CPAK types among patients with arthritis, as well as healthy people. Results A total of 29 studies (28 retrospective and 1 prospective) were included in this review, encompassing 27,660 knees in 22,342 subjects. The methodological quality of the included studies was assessed using the Hoy Risk of Bias Tool, and the quality was good. Among the healthy knees (n = 4,082), CPAK type II was predominant in Europe (41.7%) and Asia (36.7%). In contrast, among arthritic knees (n = 21,632), CPAK type I was most common in Asia (51.3%), North America (32.8%), and Europe (32.8%), while CPAK type II was prevalent in Australia (29.3%) and Africa (25.5%). Notably, the proportions of CPAK type I (P < 0.001) and II (P = 0.002) knees varied significantly across different geographic regions among arthritic knees, while no significant differences were observed among healthy knees (P = 0.48, P = 0.305). Conclusion Significant variations in CPAK distributions among arthritic knees were observed across countries, while no significant differences were observed among healthy knees. Surgeons in different regions need to make individual surgical plans according to the CPAK types of patients. Video Abstract